2007
DOI: 10.1111/j.1365-313x.2007.03248.x
|View full text |Cite
|
Sign up to set email alerts
|

TECHNICAL ADVANCE: Temperature as a determinant factor for increased and reproducible in vitro pollen germination in Arabidopsis thaliana

Abstract: SummaryDespite much effort, a robust protocol for in vitro germination of Arabidopsis thaliana pollen has been elusive. Here we show that controlled temperatures, a largely disregarded factor in previous studies, and a simple optimized medium, solidified or liquid, yielded pollen germination rates above 80% and pollen tube lengths of hundreds of microns, with both Columbia and Landsberg erecta (Ler) ecotypes. We found that pollen germination and tube growth were dependent on pollen density in both liquid and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
328
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 383 publications
(340 citation statements)
references
References 64 publications
11
328
1
Order By: Relevance
“…Pollens were collected from flowers opened day (day 0) of Col and pin8-1 plants. Subsequently they were germinated on a germination medium on a microscope slide according to Boavida and McCormick 42 . Pollen germination medium was always prepared fresh from 0.5 M stock solutions of the main components (5 mM KCl, 0.01% H 3 BO 3 , 5 mM CaCl 2 , 1 mM MgSO 4 ) using autoclaved water.…”
Section: Methodsmentioning
confidence: 99%
“…Pollens were collected from flowers opened day (day 0) of Col and pin8-1 plants. Subsequently they were germinated on a germination medium on a microscope slide according to Boavida and McCormick 42 . Pollen germination medium was always prepared fresh from 0.5 M stock solutions of the main components (5 mM KCl, 0.01% H 3 BO 3 , 5 mM CaCl 2 , 1 mM MgSO 4 ) using autoclaved water.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we show that alteration of the expression of PME48, the second most expressed PME in pollen grains, results in a strong delay in imbibition and in germination both in vivo and in vitro, as well as altered phenotypes with abnormal rates of burst tubes and two pollen tube tips emerging from the same pollen grain. The phenotype is rescued by supplementing the optimum GM (Boavida and McCormick, 2007) with 2.5 mM CaCl 2 to reach 7.5 mM. In 7.5 mM CaCl 2 , pme482/2 pollen grains imbibed and germinated normally.…”
Section: Discussionmentioning
confidence: 99%
“…In the optimal solid GM described by Boavida and McCormick (2007), 65% and 90% of wild-type pollen grains were germinated after 6 and 24 h of culture, respectively (Fig. 3A).…”
Section: Isolation and Characterization Of The Pme482/2 Homozygous Mumentioning
confidence: 99%
“…Thus, optimum temperature for some reproductive processes might reflect, indeed, species origin or adaptation. For example, while for many species native to or cultivated in temperate regions optimum temperatures in the range 15ºC-25ºC are usually recorded [examples include Arabidopsis thaliana (22ºC, Boavida and McCormick, 2007), sweet cherry (25ºC, Lewis, 1942), or almond (Prunus dulcis Mill.) and peach (16ºC and 23ºC respectively, Weinbaum et al, 1984)], optimum temperatures above 25ºC have been reported for several subtropical and tropical species such as Datura stramonium (33ºC, Buchholz and Blakeslee, 1927), Oenothera (33ºC, Lewis, 1942), groundnut (30ºC for pollen germination and 34ºC for pollen tube growth, Kakani et al, 2002) or cotton (Gossypium hirsutum L.) (from 28ºC to 32ºC, Kakani et al, 2005).…”
Section: Genetic Variation In the Reproductive Processes Under Tempermentioning
confidence: 99%